CLIPS: a radio project to turn the tide in Africa - Ogallo, Laban (Technical Centre for Agricultural and Rural Cooperation, 2003)
Reaching out to farmers and rural communities, a network of amateur radio operators supports efforts to improve communication on droughts and floods throughout the continent.